CSS-змінні: зручний інструмент для налаштування стилів на ВЕБ-сайтах - Крюкова, М. М. (ХНУРЕ, 2023)
Research of CSS-variables as well as a concept and advantages of their usage are described in this paper. Code support and update simplification, improvement of code readability and increasing of site load speed have been noted among main advantages of CSS-variables. For research purposes the website was created and styled with a help of CSS-variables having an option for changing color themes with a button press. Analysis conducted for this website has shown that CSS-variables allows to structure the code making it more readable and speeds up site loading. Potential changes in website design elements will be done quicker and more flexible.
Keywords: налаштування стилів на ВЕБ-сайтах